An alternative mean reversion test for interest rates - Ozgur Ozel; Deniz Ilalan (Central Bank Review (CBR), 2018)
A number of empirical studies assert that interest rates are governed by unit root processes rejecting any form of reversion to a long term mean by resorting to certain tests, among which the Augmented Dickey Fuller (ADF) is the most widely used one. In this study, we propose an alternative testing methodology that can be applied along with ADF test, in the sense that there are times where it can capture stationarity when the other fails to do so. Moreover, our test has more power than ADF test. As an application to real-data, we consider 10-year US and Turkish T-bond rates.
Keywords: 330; Interest rates; Unit root; Mean reversion